VALIDATING THE INTERPERSONAL MINDFULNESS IN PARENTING (IM-P) SCALE FOR PARENTS IN INDONESIA: Validasi Alat Ukur Interpersonal Mindfulness in Parenting (IM-P) pada Orang Tua di Indonesia - Khairunnisa Fahira Dumbi; Carrenina Prilly Juaninda; Luh Surini Yulia Savitri (Jurnal Ilmu Keluarga dan Konsumen, 2025)
The concept of mindful parenting, derived from the broader framework of mindfulness, has gained increasing recognition in Indonesian parenting practices over recent years. However, the Interpersonal Mindfulness in Parenting (IM-P) instrument, which possesses strong psychometric properties, has not yet been available in Bahasa. The purpose of this study is to adapt the IM-P instrument into a valid and reliable Indonesian version. The IM-P was translated and adapted into Indonesian, involving a sample of 735 parents (M = 36.63; SD = 7.354) with children aged 3 to 17 years. Using a random sampling procedure, the first sample (n = 367) was used for Exploratory Factor Analysis (EFA), while the second sample (n = 368) was used for Confirmatory Factor Analysis (CFA). The study revealed that the Indonesian version of the IM-P consists of 20 items and 4 dimensions: Emotional Awareness of Self and Child, Self-Regulation in Parenting, Non-judgmental and Compassion for Child, and Non-judgmental and Compassion for Self. Overall, the IM-P Indonesia demonstrated good reliability. Additionally, the IM-P Indonesia showed a significant negative correlation with parenting stress, except for the dimension of Non-judgmental and Compassion for Self. These findings suggest that the IM-P is a valid and reliable measure for use within the Indonesian population.